Finns den inte så får vi hitta på den! Om den kvinnliga dramatikens vara eller icke vara - Feiler , Yael (Tidskrift för genusvetenskap, 1997)
This a r t i d e scrutinizes how Margareta Garpe's plays can be seen as acts of resistance, and as conscious attemps to create women's drama. Garpe's play Alla dagar, alla nätter /All days, All Nights/ from 1992 features two sisters f ä r i n g each other. Garpe's portrayal of these two women and their relationship demonstrate Garpe's displeasure with the traditional polarised "either-or " of stereotyped gender roles. This type of displeasure is what creates the base for a development of women's drama generally.